Breeding estimation of initial alfalfa material according to green mass productivity and quality - N. S. Kravchenko; А. А. Regidin; N. G. Ignatieva (Зерновое хозяйство России, 2024)
Breeding of perennial grasses is the foundation for developing a forage base to produce high-quality livestock products. The purpose of the current study was to estimate the variability of phenotypic traits of alfalfa collection populations, as well as to identify the most promising ones in terms of possession of important agronomic traits for developing varieties that meet modern requirements of agricultural production. There have been estimated economically valuable traits of 80 alfalfa populations of various ecological and geographical origins from the collection of the FSBSI “ARC “Donskoy” for the period 2019–2023. The variety ‘Rostovskaya 90’ was used as a standard. There was determined a biochemical analysis of the green mass of alfalfa collection samples, including content of protein, fat, ash, fiber, and NFE, and there was carried out a statistical analysis of the experimental data. As a result of the research, there were identified the samples ‘Smuglyanka’ (Ukraine) – 7.9 kg/m2 , ‘Rambler’ (Canada) – 7.7 kg/m2 and ‘Stavropolskaya 430’ (Russia) – 7.6 kg/m2 with large productivity of green mass. The samples with high indicators of green mass quality ‘Tibetskaya’ (Kazakhstan), ‘Sinegibridnaya 1316’ (Russia), ‘Stavropolskaya 430’ (Russia), ‘Rhizoma’ (Canada), ‘Rambler’ (Canada), ‘VNIIOZ-16’ (Russia), ‘Smuglyanka’ (Ukraine), ‘Karlygash’ (Kazakhstan), ‘Prowler’ (USA), ‘Sarga’ (Russia), ‘G-4’ (Russia), ‘Donskaya 5’ (Russia), ‘Sin 4’ (Russia), ‘Sin 5’ (Russia) and ‘Sin 6’ (Russia) have been recommended for breeding programs to develop alfalfa varieties with large productivity of green mass and nutritional properties of dry matter.